Practical strategies for carbohydrate periodization in football - An integrated approach with reference to training periodisation - Pallotta, H. (Journal of Australian Strength and Conditioning, 2019)
Due to the dynamic demands of a football season, it is evident throughout the literature that a more systematic variation in carbohydrate intake may provide athletes with the greatest opportunity to meet the demands of training and competition.